Gerakan Jumat Nagrog Bersih to increase public awareness of environmental cleanliness - Fadila, Miftah; Kusmana, Rendy Tresna (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2024)
The village is a legal community unit with household administration based on the rights of origin and customs recognized by the central government and domiciled in the regional district. The existence of KKN in the village will train students to observe what might be developed or identify a problem that requires a solution. One of the programs that needs a solution to maintain environmental cleanliness is the Jumat Nagrog Bersih (JUNARSIH) Movement. This is done by evaluating the results of the observations made. The results show a need for re-socialization to increase public awareness about maintaining environmental cleanliness. In addition, it is necessary to collaborate with the entire potential of the community, such as informal leaders, religious leaders, Non-Governmental Organizations (NGOs), and mass media, so that this program can be more widely mobilized and feel its echo in the community. The strategies that can be carried out to carry out the JUNARSIH Movement are communication strategies, focusing on the intended target, and choosing the right form of communication to make the village community able to increase and improve the quality and quantity of environmental cleanliness.